Peran Crude Oil Washing System (COW) Pada Kapal Tanker - Prasetya Sigit (Majalah Ilmiah Bahari Jogja, 2020)
Crude Oil Washing System is a system that uses Crude Oil or crude oil as a washing medium. The cargo tanks are kept clean from the remnants of the crude oil load so that clean replacements can be loaded in the previously rinsed Tank by only making a little rinse first with water so that the effects of Pollution will be very limited. The pipes used which are connected to the loading pipes must be made of steel pipes or the like which have sufficient strength to withstand the required oil pressure, and must also be fixed (fixed) and strengthened properly. The Crude Oil Washing System must be installed permanently and completely separated from the other pipe systems except those connected to the pipe. Also the pipes must be equipped with a relief system to control the pressure in the pipe not to be excessive, the relief pipe system must be connected back to the suction part of the Supply Pump. While the benefits of using Crude Oil are already available on the ship by recirculation, effective for removing sediment and the remnants of oil attached to the tank (good carrier) and disassembled together with the load, do not cause rust and there is no possibility of water and oil emulsions to reduce the danger of pollution. All Crude Oil Washing work must be completed before the ship leaves the final unloading port. If until Crude Oil Washing is carried out between the two unloading ports in the tanks, it must remain empty for inspection at the following ports before being filled with ballast water.